Identification of Paracetamol in Jamu Pegel Linu Packaged and Jamu Gendong with TLC Standard Addition and Spectrophotometer UV-Vis - Nastiti Utami - (Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2022)
Traditional medicines that are circulated in the territory of Indonesia must have a distribution permit granted by the Head of the BPOM. However, it is excluded (not required to have a distribution permit) one of which is herbal medicine. One of the traditional medicines that are prohibited from being circulated contains Medicinal Chemicals (BKO). The BKO contained in herbal medicine is caused by the lack of knowledge of producers about the dangers of consuming medicinal chemicals uncontrolled, both in dosage and how to use them or even solely to increase sales because consumers like traditional medicinal products that react quickly to the body, 3 samples of packaged herbal medicine with the efficacy of overcoming aches and pains in the Surakarta. The test was carried out by qualitative analysis using Thin Layer Chromatography (TLC) and quantitative analysis using a UV-Vis Spectrophotometer. The results of the qualitative and quantitative test of paracetamol BKO in the sample showed negative results.